Math 5520 Lecture 28 Jeffrey Connors April 6, 2016 University of Connecticut
by user
Comments
Transcript
Math 5520 Lecture 28 Jeffrey Connors April 6, 2016 University of Connecticut
Math 5520 Lecture 28 Jeffrey Connors University of Connecticut April 6, 2016 Non-conforming FE spaces can also be considered Consider the model problem −∇ · A∇u = f , on Ω, u = 0, on ∂Ω. For conveniece, we will let A be constant and SPD. The weak problem is to find u ∈ H01 (Ω) such that a(u, v ) = L(v ), ∀v ∈ H01 (Ω). Now, consider using the following FE space: Vh = v : v |E ∈ P1 (E ), ∀E ∈ τh and v is continuous at all edge midpoints . Then Vh * H01 (Ω) (non-conforming). Break up the variational form by element We define a “discrete” variational form XZ ah (u, v ) = A∇u · ∇v dx, ∀u, v ∈ Vh + H01 (Ω). E ∈τh E Note that a(u, v ) = ah (u, v ) if u, v ∈ H01 (Ω). The FE solution uh ∈ Vh satisfies ah (uh , vh ) = L(vh ), ∀vh ∈ Vh . Now define a norm by X kw k2h = |∇w |2L2 (E ) , ∀w ∈ Vh + H01 (Ω). E ∈τh We will have coercivity (constant α1 ) and continuity (constant α2 ) of ah (·, ·) over Vh + H01 (Ω), since A is constant and SPD. The following result is a generalization of Ceá’s lemma Lemma (“Second Strang Lemma”) ku−uh kh ≤ C |ah (u, wh ) − L(wh )| inf ku − vh kh + sup vh ∈Vh kwh kh wh ∈Vh \{0} ! . Proof. Apply the triangle inequality: ku − uh kh ≤ ku − vh kh + kvh − uh kh . Then we focus on bounding the term kvh − uh kh . Apply coercivity: α1 kuh − vh k2h ≤ ah (uh − vh , uh − vh ). Then add and subtract u in the first argument; α1 kuh − vh k2h ≤ ah (u − vh , uh − vh ) + ah (uh , uh − vh ) − ah (u, uh − vh ). Proof of lemma... It follows that α1 kuh − vh k2h ≤ α2 ku − vh kh kuh − vh kh + |ah (u, uh − vh ) − L(uh − vh )| |ah (u, uh − vh ) − L(uh − vh )| ⇒ kuh − vh kh ≤ C ku − vh kh + kuh − vh kh ! |ah (u, wh ) − L(wh )| . ≤ C ku − vh kh + sup kwh kh wh ∈Vh \{0} Now use the bound with the first inequality in the proof: ku − uh kh ≤ C |ah (u, wh ) − L(wh )| ku − vh kh + sup kwh kh wh ∈Vh \{0} ! The desired result follows by taking the infimum over vh ∈ Vh . . Bounding the approximation error Assume: I Ω is convex and polygonal, I f ∈ L2 (Ω). Then H 2 -ellipticity holds for our problem; u ∈ H 2 (Ω). Set vh = Ih u in the lemma. We note next that ku − Ih ukh ≤ C h|u|H 2 (Ω) . This actually follows from our earlier interpolation error arguments; the steps bounded the error on each element and then summed over the elements. It remains to bound the consistency error term. Since u ∈ H 2 , XZ ah (u, wh ) − L(wh ) = A∇u · ∇wh − fwh dx E ∈τh = XZ E ∈τh E E − (∇ · A∇u + f ) wh dx + XZ E ∈τh ∂E (A∇u · nE ) wh dσ. Use the fact that we have a strong solution It follows that ah (u, wh ) − L(wh ) = XZ (A∇u · nE ) wh dσ. ∂E E ∈τh Denote the set of three edges of each E by SE , so e ∈ SE means that e is an edge of E . Define Z 1 w eh = wh dσ. |e| e Then ah (u, wh ) − L(wh ) = X XZ E ∈τh e∈SE since R e∈SE1 A∇u · nE1 dσ + R e∈SE2 (A∇u · nE ) (wh − w eh ) dσ, e A∇u · nE2 dσ = 0. Get into the form of error estimates over the edges Note that since Z (wh − w eh ) dσ = 0, e we can add in the constant ∇(Ih u) · nE : X XZ ah (u, wh ) − L(wh ) = A∇ (u − Ih u) · nE (wh − w eh ) dσ. E ∈τh e∈SE e Apply Cauchy-Schwarz... |ah (u, wh ) − L(wh )| X X ≤ kA∇ (u − Ih u) · nE kL2 (e) kwh − w eh kL2 (e) E ∈τh e∈SE The terms with wh − w eh are easily bounded since wh is linear. The interpolation errors are handled using previous results. Apply the estimates below and the result follows It holds that 1/2 kA∇ (u − Ih u) · nE kL2 (e) ≤ C hE |u|H 2 (E ) 1/2 kwh − w eh kL2 (e) ≤ C hE |wh |H 1 (E ) . Therefore, |ah (u, wh ) − L(wh )| ≤ C X hE |u|H 2 (E ) |wh |H 1 (E ) E ∈τh ≤ C h |u|H 2 (Ω) kwh kh . Then dividing through by kwh kh and taking the supremum over wh ∈ Vh yields the desired result.